Taxonomic notes on Castanopsis (Fagaceae, Castaneoideae) from China - Chen, Li; Li, Xin Wei; Li, Jian Qing (Phytotaxa, 2013)
The taxonomy of some Chinese Castanopsis species is clarified in the present paper. C. semifabri is accepted as the taxonomically correct name, having priority over C. ledongensis. C. wuzhishanensis is treated as a new synonym of C. semifabri. C. qiongbeiensis described from Hainan is a new synonym of the widely distributed and more variable C. chinensis. C. lantsangensis and Quercus pinfaensis are reduced to synonyms of C. ceratacantha and C. eyrei rather than synonyms of C. mekongensis and C. fargesii, respectively. The variety C. carlesii var. spinulosa is subsumed as a new synonym of C. carlesii. C. formosana is resurrected as a separate species rather than treated as a synonym of C. jucunda. In addition, an accurate description of C. wenchangensis is given to replace the inaccurate one given in Flora Reipublicae Popularis Sinicae and Flora of China.